The Effectiveness of Mode Deactivation Model Group Counseling in Improving the Emotional Wellness of Junior High School Students - Rahmadanti, Ananda Dwi; Barida, Muya; Hartini, Sri; Setyowati, Aprilia (Buletin Konseling Inovatif, 2026)
This study was motivated by the low level of emotional wellness among some junior high school students, characterized by difficulties in recognizing, understanding, and managing emotions adaptively, thereby impacting social behavior and learning processes at school. Previous studies have shown that emotion regulation-based interventions are effective in improving adolescents' emotional well-being. However, counseling interventions in schools that specifically target emotional regulation patterns to improve students' emotional wellness are still relatively limited in guidance and counseling services. Therefore, this study aims to examine the effectiveness of group counseling using the Mode Deactivation Counseling (MDC) model in improving the emotional wellness of junior high school students. This study uses a quantitative approach with a one-group pretest-posttest experimental design. The research subjects consisted of five eighth-grade students from a junior high school in Yogyakarta, Indonesia, selected using purposive sampling based on the criterion of low emotional wellness. Data were collected using an emotional wellness scale that had been tested for content validity through expert judgment and reliability. Data analysis was performed using the Wilcoxon Signed-Rank Test to determine differences in scores before and after treatment. The results show a significant difference between pretest and posttest emotional wellness scores after participating in MDC group counseling (p = 0.043 < 0.05). These findings indicate that MDC group counseling is effective in improving emotional wellness among junior high school students.